(untitled) (El-Wahat Journal for Research and Studies, 2026)
This study examines the current reality of domestic tourism in Algeria as a strategic mechanism for achieving sustainable development. Using a descriptive-analytical approach, the research analyzes tourism statistics, investment developments, and policy frameworks from 2020-2024. The findings reveal that Algeria received over 3.5 million visitors in 2024, with domestic tourists representing approximately 85% of total tourist flows. The study demonstrates that domestic tourism contributes significantly to employment creation, regional development, and economic diversification. Hotel infrastructure expanded with 47 new establishments delivering 4,687 beds in 2024, while 13 new hotel projects were launched representing 2,603 rooms. The research concludes that domestic tourism, when properly managed and promoted, serves as an effective catalyst for sustainable development, particularly in southern regions where desert tourism shows remarkable growth potential.